The Directional Hierarchical AODV (DH-AODV) routing protocol for wireless mesh networks - Mahmod, Zainab Senan; Hassan Abdalla Hashim, Aisha; Hameed, Shihab A.; Anwar, Farhat; Hassan, Wan Haslina (Institute of Electrical and Electronics Engineers Inc., 2016)
Wireless mesh networks (WMNs) can be considered as a key technology for next-generation wireless networking. However, field trials and experiments prove that the performance of WMNs still below expectations. Therefore, several challenging research issues need to be determined. The routing protocol is one of the important factors to be improved to be robust, scalable, secured and efficient. This paper aims to design and implement a routing protocol that improves the scalability of the WMNs. The Directional Hierarchical AODV (DH-AODV) routing protocol is proposed taking advantage of the existing fields of the control packets in the AODV in order to reduce the load on the network's bandwidth and to quickly detect route breakage. The proposed protocol is designed, implemented and evaluated using Qualnet Simulator. The Ad-hoc on Demand Distance Vector (AODV) is selected as a benchmark. The simulation results indicate that this enhanced routing protocol can 47% reduce the end-to-end delay of data packets, improve the throughput by 11.2%, and decrease the packet loss rate 20% less than the standard AODV.